The prevalence of developmental defects of enamel in people with cystic fibrosis: a systematic review - Fiona O'Leary; Niamh Coffey; Martina Hayes; Francis Burke; Mairéad Harding; Barry Plant (BMC, 2024)
Abstract Background Oral health impacts systemic health, individual well-being, and quality of life. It is important to identify conditions that may exacerbate oral disease to aid public health and policy development and promote targeted patient treatment strategies. Developmental defects can increase an individual's risk of dental caries, hypersensitivity, premature tooth wear, erosion, and poor aesthetics. As part of an ongoing study assessing oral health in adults with cystic fibrosis at Cork University Dental School and Hospital, a systematic review of available literature was conducted to assess the prevalence of enamel defects in people with cystic fibrosis. Aims To critically evaluate the literature to determine if the prevalence of developmental defects of enamel is higher in people with cystic fibrosis (PwCF). Methods Data Sources: Three online databases were searched Embase, Scopus, and Web of Science Core Collection. Studies that examined an association between cystic fibrosis and developmental defects of enamel were included in this systematic review. Results The initial search identified 116 publications from the following databases Embase, Web of Science Core Collection, and Scopus. Eleven studies were included for qualitative analysis. Nine studies concluded that PwCF had a higher prevalence of enamel defects than control people and one study found no difference in cystic fibrosis (CF) status. All studies had a risk of bias that may influence study results and their interpretation. Conclusions The results of the systematic review show a consistent pattern that PwCF have a higher prevalence of DDE than people without CF. Genetic dysfunction, chronic systemic infections, and long-term antibiotic use are possible aetiological causes. This review highlights the need for future studies to investigate if DDEs are caused by the underlying CFTR mutation or as a consequence of disease manifestations and/or management.